Sustainable and Tunable Synaptic Electrolyte-Gated Organic Field-Effect Transistors (EGOFETs) for Light Adaptive Visual Perceptive Systems - Serghiou, Theodoros; Fernandes, José Diego [UNESP]; Karthikeyan, Vaithinathan; Assi, Dani S.; Vieira, Douglas Henrique [UNESP]; Alves, Neri [UNESP]; Kettle, Jeff (Wiley, 2025)
The recent advances in optic neuromorphic devices have led to a subsequent rise in the development of energy-efficient artificial-vision systems. While the energy consumption of such devices is known to be much lower than conventional vision systems, it is known that manufacturing accounts for the largest share of the climate impact in microelectronics, dominating over the product use phase. Thus, there is a need to develop sustainable manufacturing processes and to adopt low-impact materials for hardware solutions of the future. In this study, an Electrolyte-Gated Organic Field-effect Transistor (EGOFET) is experimentally demonstrated for the implementation of a high-performing synaptic optical sensor using sustainable materials that degrade to benign products at the End of Life (EoL). The device shows remarkable light response with maximum Paired-Pulse Facilitation (PPF) Index of up to 151% at a light power density of 38 µW cm−2, which enables artificial synaptic applications with an average power consumption as low as 2.4 pJ for each training process, representing one of the best among the reported results. To demonstrate the tunability of the vision system, an ensemble decision tree is used to enable the EGOFET to distinguish and remember different primary colors at different power densities with 95.6% accuracy.
Keywords: electro-gated transistors; neuromorphic imaging system; optical synaptic devices; organic phototransistors; sustainable materials